CONCEPTUAL ANALYSIS THROUGH COGNITIVE‑STYLISTIC METHODOLOGY - Liu XUEMEI (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The study takes a cognitive-stylistic approach to advance conceptual analysis, demonstrating how abstract conceptual structures are realised and modified within actual discourse. Drawing on extensive, carefully curated corpora and rigorous close analysis, the research integrates cognitive theories of metaphor, frame semantics and foregrounding to identify recurring patterns of linguistic realisation. The study demonstrates how metaphorical mappings organise inferential structures, how frames guide interpretative processes, and how stylistic foregrounding selectively highlights elements to shape understanding and evoke emotion. In terms of methodology, the paper advocates closer integration of corpus evidence with fine-grained qualitative analysis, as well as explicit links between cognitive models and stylistic description. The proposed refinements include operationalised criteria for identifying conceptual instantiations, protocols for balancing frequency data with contextual interpretation and pedagogical strategies for teaching analytical skills across disciplines. By combining theoretical insight with practical techniques, the study provides a replicable framework for interdisciplinary research and classroom practices that help students to recognise and manipulate conceptual patterns in language. It also outlines avenues for future empirical validation studies.